Nitrogen, phosphorous, and potassium uptakes of organically grown sweet corn on coastal Entisols - Muktamar, Z.; Fahrurrozi, F.; Sudjatmiko, S.; Setyowati, N.; Chozin, M. (International Journal of Agricultural Technology, 2021)
Results indicated that nutrient uptakes by organically grown sweet corn in coastal land of Entisols were very low; 0.44 to 0.67 g plant-1 for N, 0.35 to 0.61 g plant-1 for P, and 0.41 to 0.63 g plant-1 for K. In addition, nutrient tissue contents were also very low; 1.35 to 1.75 % for N, 1.18 to 1.58 % for P, and 1.29 to 1.68 % for K. It is concluded that after a one year of establishing organically growing environment on coastal Entisols, the use of LOF increased N and K tissue contents, but did not increase N, P and K uptakes, as well as P tissue content of sweet corn. For production purposes of sweet corn in coastal Entisols, it is imperative to pay attention to the amount of nutrient supply into the soil to assure sufficient nutrient availability for the plants